Improving Village Bookkeeping and Accountability Report (SPJ) Competence through Local Government Initiatives in Kaur District - Melsi Febrianti; Hesti Marni; Patra Agung Syaputra; Titi Darmi (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2026)
This study aims to analyze the effectiveness of the training conducted by the Regional Inspectorate of Kaur District in improving the competence of village officials in financial management, particularly in bookkeeping and the preparation of the Accountability Report (SPJ). The method used is a descriptive qualitative approach with data collection through in-depth interviews, participatory observation, and document analysis. The research informants consisted of 12 village officials, village heads, and officials from the Regional Inspectorate of Kaur District. The results show that although training has been conducted, many village officials still struggle to understand and implement the procedures for bookkeeping and preparing SPJ according to the applicable standards. The training, which is more theoretical and lacks practical involvement, is one of the factors causing these difficulties. The findings also revealed that many villages still use manual systems for financial recording, which risks creating discrepancies in financial reports. This study recommends that the training for village officials be more practice-based and encourages the adoption of information technology in village financial management to improve transparency and accountability. More practical training is expected to enhance the competence of village officials in accountable and efficient financial management.